Religious Pluralism and the Modern World
XIV, 283 p.
Keywords: A fascinating collection of essays by leading scholars in the field engage with the idea of religious pluralism mooted by John Hick to offer incisive insights on religious pluralism and related themes and to address practical aspects such as interreligious spirituality and worship in a multi-faith context.